ANALISIS PEMBIAYAAN KESEHATAN KELUARGA MISKIN DI KABUPATEN BUTON PROVINSI SULAWESI TENGGARA = HEALTH FINANCING ANALYSIS OF POOR FAMILIES ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Background: Health financing for poor families at Buton District is at present subsidized by central government. However, it is worrying that such subsidy is only temporary. As a consequence of local autonomy implementation regulated in Enactment No. 32, 2004, local government is obliged to develop health financing system in the area in order to be more efficient and effective. The study was meant to get on overview of need of fund and stakeholderâs perception about health maintenance program for poor families. Methods: The study was a non-experimental type which used case study design. Unit of analysis was Buton District. Subject of the study were 13 stakeholders who look part in making decision on health financing policy for poor families at Buton District. The study was conducted in two stages